Analisis Kemampuan Membaca Pemahaman Siswa IV Sekolah Dasar di SDN 0404 Janjiraja - Hafni Laila Sari Siregar; Chandra Chandra; Inggria Kharisma (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to examine the reading comprehension abilities of fourth-grade elementary students. The primary goals are to assess the level of students' comprehension skills, investigate the underlying factors contributing to their difficulties in understanding texts, and develop applicable strategies to address these challenges. This study employed a qualitative approach using a case study method. The participants were four students from the fourth grade. Data were gathered through various techniques, including observation, interviews, testing, and documentation. The findings indicated that students' reading comprehension abilities remained relatively weak. In terms of interpreting the meaning of words and expressions used by the author, students demonstrated performance at a moderate level. However, regarding the ability to understand both explicit and implicit meanings, as well as to draw conclusions from the text, their performance fell into the low or inadequate category. The factors that influence this low ability come from both internal and external factors. To overcome this problem, it is recommended that teachers motivate students more, manage the class more effectively, and apply reading comprehension strategies such as Know, Want, Learn (KWL).